Quality assessment for methodological aspects of microplastics analysis in soil - Praveena, Sarva Mangala; Aris, Ahmad Zaharin; Singh, Veer (Elsevier, 2022)
Over the last several years, a number of studies have concentrated on the occurrence, potential sources, and ecological implications of soil systems. However, the studies’ methodological aspects have received little attention. Thus, this study performed a quality assessment for the methodological aspects of soil microplastics studies by adopting the Criteria for Reporting and Evaluating Ecotoxicity Data (CRED) evaluation method. A total of 35 soil microplastic studies have been evaluated in terms of methodological aspects using 13 criteria, namely, sampling methods and strategy, sample processing and storage, sample size, laboratory preparation, clean air conditions, chemical purity, negative control, positive control, sample pre-treatment, microplastics particle data, particle size, particle shape and polymer type identification. The quality assessment findings indicated that no study scored a maximum of two in all criteria, reiterating the urgent need for enhanced quality assurance for future soil microplastics studies. The average quality assessment scores in soil microplastics studies also indicated that the conditions requiring the most improvement involve both the criteria of positive controls and the criteria of clean air conditions. With a value of zero in 13 assessed criterion, the relevance of the study's findings in environmental risk assessment was restricted, suggesting that future studies should consider strengthening the implementation and reporting of QA/QC protocol. Adoption of proper quality assurance and contamination control measures will guarantee high data quality and establish confidence in the study's findings, which allow for reproducibility and comparability as well as acceptability to be utilized in risk assessments.